Cerdas Digital Sehat Mental,Membangun Generasi Muda yang Bijak dan Produktif di Era Digital pada Karang Taruna Diponegoro: Digitally Smart, Mentally Healthy, Building a Wise and Productive Young Generation in the Digital Era at Karang Taruna Diponegoro - Rimawati, Elistya; Vinahapsari, Cinthia Annisa; Saptomo, Wawan Laksito Yuly; Azizah, Umi Fajar; Adji, Aulia Gustin San; Marsudi, Lexsa Sifa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This Community Engagement Program aims to address three main problems faced by the Diponegoro Youth Organization (Karang Taruna): a lack of digital literacy and data security, low awareness of mental health, and the suboptimal use of technology for productivity. To tackle these issues, the implementing team applied a participatory approach through a detailed series of activities, covering: Initiation and Collaboration, Training Program Preparation, Training Implementation (in the form of workshops), Intensive Mentoring, and Monitoring and Evaluation The themes for the intensive workshops and mentoring consisted of three main issues: Mental Resilience in the Digital Era, Affiliate Digital Marketing, and Personal Data Security. This program has produced several key outputs, both tangible and social. Three guidebooks (Emotional Intelligence in the FOMO Era; Affiliate Marketing: Turn Social Media into a Money Machine; and Early Detection, Self-Protection), instructional videos, and an X-Banner for the